FOXO3: A master switch for regulating tolerance and immunity in dendritic cells - Watkins, Stephanie K. (Landes Bioscience, 2012)
Recent findings demonstrate that dendritic cells in prostate tumors induce immune tolerance in tumor antigen-specific CD8(+) T cells. We propose that DC tolerogenicity can be regulated by expression of Foxo3; silencing Foxo3 expression enhances anti-tumor immune responses and renders FOXO3 a potential target for immunotherapy.